Results of surgical treatment of ulnar nerve schwannomas arising from upper extremity: Presentation of 15 cases with review of literature - Aksoy, Alper; Sır, Emin (Journal of Surgery and Medicine, 2019)
Aim: Schwannomas are the most common benign tumors of upper extremities. The diagnosis of peripheral nerve lesions on clinical history, physical examination, and radiologic tests. Magnetic resonance imaging (MRI) is one of the best to use on schwannomas radiologic test. The aim of this study is to evaluate patients who are diagnosed with schwannomas on the ulnar nerve by mutual agreement between pathology and MRI. Methods: Retrospective cohort study was designed. From January 2011 – December 2016, 15 patients who had surgery ulnar nerve mass and had been diagnosed schwannomas were included in the study. The anatomical classification was at 6 arms, 4 elbows and 5 forearms. Before surgery, all patients were diagnosed with nerve mass through by MRI. Patients were operated under regional anesthesia and microscope. Results: All patients have diagnosed with histopathological schwannomas. All tumors were observed isointense in T1-weighted images and hyperintense in T2-weighted ones. Nerve injuries and motor deficit were not observed after surgery. All tumors were enucleated without harming any nerve fibers. The postoperative mean follow-up period was 12.4 months (9 – 29). In the early postoperative period, paresthesia, pain, and hypoesthesia were noted in 10 patients. Neurological symptoms were recovered in postoperative 5 months. Conclusions: Schwannomas are solitary and benign tumors that are shown on the median and ulnar nerve. MRI and high-resolution ultrasonography are the big help to plan the treatment before the surgery. They are removed as intracapsular with acceptable complication ratio. Removing schwannomas can cause some sensational deficit such as pain and paresthesia but these complications are spontaneously decreased.